2015
DOI: 10.1890/14-1616.1
|View full text |Cite
|
Sign up to set email alerts
|

Predator cannibalism can intensify negative impacts on heterospecific prey

Abstract: Although natural populations consist of individuals with different traits, and the degree of phenotypic variation varies among populations, the impact of phenotypic variation on ecological interactions has received little attention, because traditional approaches to community ecology assume homogeneity of individuals within a population. Stage structure, which is a common way of generating size and developmental variation within predator populations, can drive cannibalistic interactions, which can affect the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 24 publications
(50 citation statements)
references
References 75 publications
2
48
0
Order By: Relevance
“…Trait‐mediated indirect effects through predator growth can occur when the population of the predator species is size‐structured, for example, if cannibalism, a size‐ dependent behavior, enhances the growth of the cannibalistic individuals. In the same amphibian predator–prey system, Takatsu and Kishida () found that cannibalism by large salamander hatchlings on small conspecific hatchlings greatly enhances the growth of cannibalistic salamanders, and these bigger salamanders subsequently exert intensive predation pressure on large tadpoles. These results reported by Takasu and Kishida (2015), together with the present results, suggest that trait‐meditated apparent competition between prey items can occur via predator growth: one prey item is vulnerable to predation and causes the predator to grow rapidly, because it is a nutrient‐rich food source, and the other is less vulnerable to predation unless the predator grows bigger.…”
Section: Discussionmentioning
confidence: 99%
“…Trait‐mediated indirect effects through predator growth can occur when the population of the predator species is size‐structured, for example, if cannibalism, a size‐ dependent behavior, enhances the growth of the cannibalistic individuals. In the same amphibian predator–prey system, Takatsu and Kishida () found that cannibalism by large salamander hatchlings on small conspecific hatchlings greatly enhances the growth of cannibalistic salamanders, and these bigger salamanders subsequently exert intensive predation pressure on large tadpoles. These results reported by Takasu and Kishida (2015), together with the present results, suggest that trait‐meditated apparent competition between prey items can occur via predator growth: one prey item is vulnerable to predation and causes the predator to grow rapidly, because it is a nutrient‐rich food source, and the other is less vulnerable to predation unless the predator grows bigger.…”
Section: Discussionmentioning
confidence: 99%
“…Occasionally, R. pirica frog tadpoles can feed on living animal prey if the prey is small and weak (e.g., amphibian larvae in dying condition). Hynobius retardatus salamander larvae, by contrast, are strictly carnivorous, preying mainly on amphibian larvae including R. pirica tadpoles and conspecifics (Takatsu & Kishida, ).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the variably sized tadpole populations should lead to an increase in the abundance of zooplankton when newts are present. In some systems, however, the enhanced growth of predators may enhance their capacity to feed upon alternative prey, resulting in greater predation pressure (Takatsu & Kishida, ); a form of apparent competition (Holt, ), although in our study, there are no alternative prey that are larger than the tadpoles. Finally, changes in tadpole abundance and foraging may also indirectly influence zooplankton populations.…”
Section: Introductionmentioning
confidence: 76%